Apoptotic Platelet Events Are Not Observed in Severe von Willebrand Disease-Type 2B Mutation p.V1316M - Berrou, Eliane (PLoS One, 2015)
Thrombocytopenia and increased platelet clearance observed in von Willebrand disease-type 2B (VWD-2B) may be explained by platelet apoptosis triggered by the constitutive binding of VWF to its receptor, glycoprotein Ib (GPIb). Apoptosis was assessed in platelets from two patients with a severe VWD-2B mutation VWF/p.V1316M and from mice transiently expressing VWF/p.V1316M. We now report that the VWD-2B mutation VWF/p.V1316M which binds spontaneously to its receptor GPIbα does not induce apoptosis. In 2 unrelated patients (P1 and P2) exhibiting different VWF plasma levels (70% and 36%, respectively, compared with normal pooled human plasma given as 100%), inner transmembrane depolarization of mitochondria, characteristic of apoptotic events was undetectable in platelets, whether washed or in whole blood. No or a moderate phosphatidyl serine (PS) exposure as measured by annexin-V staining was observed for P1 and P2, respectively. Expression of pro-apoptotic proteins Bak and Bax, and caspase-3 activity were similar to control platelets. In the VWD-2B mouse model expressing high levels of mVWF/p.V1316M (423%), similar to what is found in inflammatory pathologies, no significant difference was observed between mice expressing mVWF/WT and mVWF/p.V1316M. These results strongly argue against apoptosis as a mechanism for the thrombocytopenia of severe VWD-2B exhibiting the VWF/p.V1316M mutation.